Spectral analysis of basaltic asteroids observed by the Gaia space mission. Issue 2 (24th November 2022) - Oszkiewicz, Dagmara; Klimczak, Hanna; Carry, Benoit; Penttilä, Antti; Popescu, Marcel; Krüger, Joachim; Aron Keniger, Marcelo
ABSTRACT: There is a great deal of scientific interest in characterizing the basaltic asteroids (spectrally classified as V-types), as they are the key to understanding planetesimal formation and evolution in the early Solar system. These have long been recognized as parts of the crusts of fully differentiated planetesimals. Thus, their multiplicity, distribution, and physical characteristics are crucial for providing context for and constraining the theoretical evolution models of the Solar system. In this work, we perform spectral analysis with an extended data set of spectral measurements from the ESA Gaia mission Data Release 3, thus increasing the sample size of the analysed V-types by more than three times as compared to the literature. Using the data provided by Gaia, we identified ∼2000 possible V-type asteroids. About 350 of them successfully pass our data validation criteria. This sample includes 31 new V-type asteroids beyond 2.5 au and 6 in the Phocaea region. We confirm that the V-type asteroids in the middle and outer part of the main belt show distinct spectral properties compared to typical vestoids. In the inner main belt, we found a great diversity of spectral parameters among the V-types in all populations. Number of asteroids show band depths even greater than that of (1459) Magnya. Furthermore, some objects present 0.9 μm band-centres more than one standard deviation away from the typical value for vestoids. However since the DR3 band centres are often overestimated, those findings are to be confirmed. Overall our results indicate that the inner main belt may contain remnants of multiple differentiated planetesimals, not just (4) Vesta.